Math Doubts

Proof of Heron’s formula

The Hero’s or Heron’s formula can be derived in geometrical method by constructing a triangle by taking $a$, $b$, $c$ as lengths of the sides and $s$ as half of the perimeter of the triangle.

$\Delta PQR$ is a triangle. The lengths of sides of triangle $\overline{PQ}$, $\overline{QR}$ and $\overline{PR}$ are $a$, $b$ and $c$ respectively. The perimeter of the triangle is $a+b+c$ but it is denoted by $2s$ in heron’s formula.

heron's formula triangle construction
  1. $PQ \,=\, a$
  2. $QR \,=\, b$
  3. $PR \,=\, c$
  4. $2s \,=\, a+b+c$

Draw a perpendicular line to side $\overline{PR}$ from point $Q$ and it intersects the side $\overline{PR}$ at point $S$. Take, the length of the sides $\overline{QS}$ and $\overline{PS}$ are $h$ and $x$ respectively, then the length of the side $\overline{SR}$ is equal to $c-x$.

  1. $QS \,=\, h$
  2. $PS \,=\, x$
  3. $SR \,=\, c-x$

Relation between sides of triangles

The $\Delta SPQ$ and $\Delta SRQ$ are two right triangles, which have $\overline{QS}$ as a common opposite side. Now, write the relation between sides of each triangle by the Pythagorean Theorem.

heron's formula triangle

According to $\Delta SPQ$

$a^2 \,=\, x^2+h^2$

$\implies$ $h^2 \,=\, a^2-x^2$

According to $\Delta SRQ$

$b^2 \,=\, (c-x)^2+h^2$

$\implies$ $h^2 \,=\, b^2-(c-x)^2$

Now, replace the $h^2$ by its equivalent value as per right triangle $SPQ$. Then, simplify the algebraic expression to find the value of the $x$.

$\implies$ $a^2-x^2$ $\,=\,$ $b^2-(c-x)^2$

$\implies$ $a^2-x^2$ $\,=\,$ $b^2-(c^2+x^2-2cx)$

$\implies$ $a^2-x^2$ $\,=\,$ $b^2-c^2-x^2+2cx$

$\implies$ $a^2-b^2+c^2$ $\,=\,$ $x^2-x^2+2cx$

$\implies$ $\require{cancel} a^2-b^2+c^2$ $\,=\,$ $\cancel{x^2}-\cancel{x^2}+2cx$

$\implies$ $a^2-b^2+c^2 \,=\, 2cx$

$\implies$ $2cx \,=\, a^2-b^2+c^2$

$\,\,\, \therefore \,\,\,\,\,\,$ $x \,=\, \dfrac{a^2-b^2+c^2}{2c}$

Find the height of the Right triangle

In PQR, the base of the triangle is PR and it is equal to c but the height of the triangle is unknown. For calculating the area of a triangle, it is required to know both base and height of triangle. So, let us evaluate the height of the triangle from the following equation, which was derived in previous step from the $\Delta SPQ$.

$h^2 \,=\, a^2-x^2$

Now, substitute the value of $x$ in this equation to find the height of the triangle.

$\implies$ $h^2$ $\,=\,$ $a^2-\Bigg(\dfrac{a^2-b^2+c^2}{2c}\Bigg)^2$

$\implies$ $h^2$ $\,=\,$ $\Bigg(a+\dfrac{a^2-b^2+c^2}{2c}\Bigg)$ $\Bigg(a-\dfrac{a^2-b^2+c^2}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{a\times 2c + (a^2-b^2+c^2)}{2c}\Bigg)$ $\Bigg(\dfrac{a\times 2c -(a^2-b^2+c^2)}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{2ac+a^2-b^2+c^2}{2c}\Bigg)$ $\Bigg(\dfrac{2ac-a^2+b^2-c^2}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{a^2+c^2+2ac-b^2}{2c}\Bigg)$ $\Bigg(\dfrac{-a^2-c^2+2ac+b^2}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{a^2+c^2+2ac-b^2}{2c}\Bigg)$ $\Bigg(\dfrac{-(a^2+c^2-2ac)+b^2}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{(a+c)^2-b^2}{2c}\Bigg)$ $\Bigg(\dfrac{-(a-c)^2+b^2}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{(a+c)^2-b^2}{2c}\Bigg)$ $\Bigg(\dfrac{b^2-(a-c)^2}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{(a+c+b)(a+c-b)}{2c}\Bigg)$ $\Bigg(\dfrac{(b+(a-c))(b-(a-c))}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{(a+b+c)(a+c-b)}{2c}\Bigg)$ $\Bigg(\dfrac{(b+a-c)(b-a+c)}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{(a+b+c)(a+c-b)}{2c}\Bigg)$ $\Bigg(\dfrac{(a+b-c)(-a+b+c)}{2c}\Bigg)$

Now, express the each factor in terms of perimeter.

  1. $a+b+c = 2s$
  2. $a+c-b = a+c-b+b-b$
    $\implies$ $a+c-b = a+b+c-b-b$
    $\implies$ $a+c-b = 2s-2b$
    $\implies$ $a+c-b = 2(s-b)$
  3. $a+b-c = a+b-c+c-c$
    $\implies$ $a+b-c = a+b+c-c-c$
    $\implies$ $a+b-c = 2s-2c$
    $\implies$ $a+b-c = 2(s-c)$
  4. $-a+b+c = -a+b+c+a-a$
    $\implies$ $-a+b+c = a+b+c-a-a$
    $\implies$ $-a+b+c = 2s-2a$
    $\implies$ $-a+b+c = 2(s-a)$

Now, simplify this algebraic expression by substituting the equivalent value of every factor.

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{(2s)(2(s-b))}{2c}\Bigg)$ $\Bigg(\dfrac{(2(s-c))(2(s-a))}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{2s \times 2(s-b)}{2c}\Bigg)$ $\Bigg(\dfrac{2(s-c) \times 2(s-a)}{2c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{2 \times s \times 2(s-b)}{2 \times c}\Bigg)$ $\Bigg(\dfrac{2 \times (s-c) \times 2(s-a)}{2 \times c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\require{cancel} \Bigg(\dfrac{\cancel{2} \times s \times 2(s-b)}{\cancel{2} \times c}\Bigg)$ $\Bigg(\dfrac{\cancel{2} \times (s-c) \times 2(s-a)}{\cancel{2} \times c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\Bigg(\dfrac{2s(s-b)}{c}\Bigg)\Bigg(\dfrac{2(s-a)(s-c)}{c}\Bigg)$

$\implies$ $h^2$ $\,=\,$ $\dfrac{2s(s-b) \times 2(s-a)(s-c)}{c \times c}$

$\implies$ $h^2$ $\,=\,$ $\dfrac{4s(s-a)(s-b)(s-c)}{c^2}$

$\implies$ $h$ $\,=\,$ $\pm \sqrt{\dfrac{4s(s-a)(s-b)(s-c)}{c^2}}$

According to Physics, the height is a positive factor. So, just consider positive value as the height in this case.

$\implies$ $h$ $\,=\,$ $\sqrt{\dfrac{4s(s-a)(s-b)(s-c)}{c^2}}$

$\implies$ $h$ $\,=\,$ $\sqrt{\dfrac{4}{c^2} \times s(s-a)(s-b)(s-c)}$

$\implies$ $h \,=\, \sqrt{\dfrac{2^2}{c^2} \times s(s-a)(s-b)(s-c)}$

$\implies$ $h \,=\, \sqrt{\Big(\dfrac{2}{c}\Big)^2 \times s(s-a)(s-b)(s-c)}$

$\implies$ $h \,=\, \sqrt{\Big(\dfrac{2}{c}\Big)^2} \times \sqrt{s(s-a)(s-b)(s-c)}$

$\implies$ $h \,=\, \dfrac{2}{c} \times \sqrt{s(s-a)(s-b)(s-c)}$

Evaluate area of the triangle

Now, use the cross multiplication for bringing the factor $\dfrac{2}{c}$ to left hand side of the equation.

heron's formula triangle

$\implies$ $c \times h \,=\, 2 \times \sqrt{s(s-a)(s-b)(s-c)}$

$\implies$ $\dfrac{c \times h}{2} \,=\, \sqrt{s(s-a)(s-b)(s-c)}$

$\implies$ $\dfrac{1 \times c \times h}{2} \,=\, \sqrt{s(s-a)(s-b)(s-c)}$

$\implies$ $\dfrac{1}{2} \times c \times h \,=\, \sqrt{s(s-a)(s-b)(s-c)}$

According to Geometry, the half of the product of base and height of the triangle is the area of the respective triangle.

$\,\,\, \therefore \,\,\,\,\,\,$ $A \,=\, \sqrt{s(s-a)(s-b)(s-c)}$

Thus, a mathematician Hero of Alexandria derived the area of a triangle in mathematics. It is denoted by either $A$ or $\Delta$ in mathematics. It is called as Heron’s formula or Hero’s formula.

Math Doubts
Math Doubts is a best place to learn mathematics and from basics to advanced scientific level for students, teachers and researchers. Know more
Follow us on Social Media
Math Problems

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.

Learn more